2017
DOI: 10.3389/fnmol.2016.00167
|View full text |Cite
|
Sign up to set email alerts
|

Endomorphin-2 Inhibition of Substance P Signaling within Lamina I of the Spinal Cord Is Impaired in Diabetic Neuropathic Pain Rats

Abstract: Opiate analgesia in the spinal cord is impaired in diabetic neuropathic pain (DNP), but until now the reason is unknown. We hypothesized that it resulted from a decreased inhibition of substance P (SP) signaling within the dorsal horn of the spinal cord. To investigate this possibility, we evaluated the effects of endomorphin-2 (EM2), an endogenous ligand of the μ-opioid receptor (MOR), on SP release within lamina I of the spinal dorsal horn (SDH) in rats with DNP. We established the DNP rat model and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 84 publications
(145 reference statements)
0
11
0
Order By: Relevance
“…Although targeting KCNQ2/3/5 channels in DRG neurons is a promising novel approach for relieving diabetic neuropathic pain as shown in our present study, the central mechanism also needs to be explored because of the central sensitization induced indirectly by peripheral nociceptive signaling transmission or directly by high glucose challenges. Upregulation of inflammatory cytokines, 50 alteration of proinflammatory neuropeptides 51 and N-methyl-D-aspartate receptor phosphorylation in spinal dorsal horn, 29 activation of anterior cingulate cortex, 28 and brain-based facilitatory pain mechanism 52 contribute to diabetic neuropathic pain. Combined peripheral and central targeting approach may represent the potential strategy on relieving diabetic neuropathic pain in future.…”
Section: Discussionmentioning
confidence: 99%
“…Although targeting KCNQ2/3/5 channels in DRG neurons is a promising novel approach for relieving diabetic neuropathic pain as shown in our present study, the central mechanism also needs to be explored because of the central sensitization induced indirectly by peripheral nociceptive signaling transmission or directly by high glucose challenges. Upregulation of inflammatory cytokines, 50 alteration of proinflammatory neuropeptides 51 and N-methyl-D-aspartate receptor phosphorylation in spinal dorsal horn, 29 activation of anterior cingulate cortex, 28 and brain-based facilitatory pain mechanism 52 contribute to diabetic neuropathic pain. Combined peripheral and central targeting approach may represent the potential strategy on relieving diabetic neuropathic pain in future.…”
Section: Discussionmentioning
confidence: 99%
“…Insular tissues from four groups (sham, TNBS POD 7, 14 and 28 groups) were harvested in cold artificial cerebrospinal fluid (ACSF). Total protein (for VGluT1, NR2B and GluR1 assays) was prepared according to our previous study [33]. Membrane and cytoplasmic proteins (for NR2B, pNR2B, GluR1 and pGluR1 assays) were separated by Minute™ Plasma Membrane Protein Isolation Kit (Invent Biotechnologies, EdenPrairie, MN, USA) [34].…”
Section: Methodsmentioning
confidence: 99%
“…EM1 and EM2 have been shown to be involved in various rodent models of pain. A study using the complete Freund's adjuvant (CFA)-induced inflammatory pain model elucidated the mechanisms underlying the antinociception effect of EM2 in inflammatory pain in the spinal based on the following set of observations [94]: ① EM2 could significantly alleviate both mechanical and thermal hyperalgesia in the CFA rats; ② EM2 could serve as an functional antagonist of neurokinin-1 receptors (NK1Rs), which are specific receptors for substance P (SP); ③ a coexistence of MOR/SP was found in DRG neurons; and ④ EM2 induced NK1R internalization in CFA-induced inflammatory pain. It was concluded that the analgesic influences of EM2 might be through binding to MORs to suppress the release of SP.…”
Section: Involvement Of Ems In the Transmission And Modulation Of Noxmentioning
confidence: 99%
“…Intracerebroventricular injection of EMs could improve PDN [99]. This down-regulation of endogenous antinociception may be due to the decreased inhibition of SP signalling resulting from the decreased presynaptic EM2 and MOR expression [94,98].…”
Section: Involvement Of Ems In the Transmission And Modulation Of Noxmentioning
confidence: 99%